2012
DOI: 10.2106/jbjs.k.01256
|View full text |Cite
|
Sign up to set email alerts
|

Combined Glenoid Anteversion Osteotomy and Tendon Transfers for Brachial Plexus Birth Palsy

Abstract: In patients with severe glenohumeral dysplasia, glenoid realignment osteotomy in conjunction with soft-tissue rebalancing permits maintenance of joint reduction and functional improvement in the short term. In our view, external rotation osteotomy of the humerus is no longer the only surgical option for these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 22 publications
2
11
0
4
Order By: Relevance
“…A complete description of our indica tions for shoulder reconstruction and the results obtained is published elsewhere. 26 It is interesting that all three studies demonstrate that of a group of patients identified as having sufficient shoul der imbalance and contractures to warrant Botox treatments, over twothirds achieved satisfactory balance and stability with Botox and casting, to the endpoint of avoiding surgical balancing pro cedures. In the absence of a randomized control group, it is impossible to identify whether Botox had a favorable contribution to this outcome in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…A complete description of our indica tions for shoulder reconstruction and the results obtained is published elsewhere. 26 It is interesting that all three studies demonstrate that of a group of patients identified as having sufficient shoul der imbalance and contractures to warrant Botox treatments, over twothirds achieved satisfactory balance and stability with Botox and casting, to the endpoint of avoiding surgical balancing pro cedures. In the absence of a randomized control group, it is impossible to identify whether Botox had a favorable contribution to this outcome in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, combined glenoid anteversion osteotomy and tendon transfers have been described 47 in patients with Waters type III, IV, or V glenohumeral dysplasia. This study showed improvement in passive and active external rotation, Mallet scores, glenoid retroversion, and percentage of the humeral head anterior to the midscapular line in their early outcome data.…”
Section: Shoulder Treatmentmentioning
confidence: 99%
“…Описанные в литературе методы хирургиче-ского лечения данной патологии можно разделить на следующие группы: 1) мышечные пластики, релизы мышц, направ-ленные на восстановление мышечного баланса между наружными и внутренними ротатора-ми плеча; 2) восстановление анатомических соотношений в суставе путем выполнения различных вари-антов остеотомий лопатки, ключицы, вправле-ния головки плечевой кости; 3) устранение порочного положения конечно-сти без изменения соотношений в плечевом суставе (деротационная остеотомия плечевой кости); 4) мышечные пластики в сочетании с деротаци-онной остеотомией плечевой кости; 5) мышечные пластики в сочетании с остеотоми-ей лопатки [2,6,[11][12][13][14][15][16]. При фиксированных внутриротационных кон-трактурах плеча R.S.…”
Section: Introductionunclassified
“…Bae (2005), сухо-жильно-мышечные пластики (транспозиция ши-рочайшей и большой круглой мышц на наружные ротаторы плеча с одновременным удлинением мышц или без него) позволяют в значительной степени улучшить функцию плечевого сустава, препятствуют прогрессированию дисплазии пле-чевого сустава, однако ремоделирования сустава не происходит, даже если операция была выпол-нена у пациента раннего возраста [12]. E. Dodwell et al (2012) рекомендуют выполнять остеотомию шейки лопатки с внедрением аутотрансплантата из ости лопатки или акромиона в сочетании со слайдом подлопаточной мышцы и транспозици-ей широчайшей и большой круглой мышц на на-ружные ротаторы плеча [16]. Данная операция в большинстве случаев дает возможность изме-нять положение суставной поверхности лопатки в пространстве без ремоделирования его сустав-ной поверхности.…”
Section: Introductionunclassified
See 1 more Smart Citation